2008
DOI: 10.1002/jmri.21450
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying cerebral changes in adolescence with MRI and deformation based morphometry

Abstract: Purpose: To identify and quantify structural changes in the maturing brain between childhood and adolescence. Materials and Methods:Two three-dimensional T1-weighted MR volumes of the brain were acquired from eight subjects, 6 to 7 years apart. The subjects were 9 to 12 years old on the first scan and 15 to 19 years old on the second scan. The MR scans were converted to one millimeter isotropic volumes, globally aligned with a rigid transform, inhomogeneity corrected, and nonrigid deformation fields between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Gogtay et al, (2004) found that changes in gray matter volume follow a non-linear pattern across different brain regions, with loss of gray matter density (either through synaptic pruning or intracortical myelination - Paus, 2005) to dorsolateral prefrontal cortex and posterior superior temporal gyrus only evident after age 16-17 years in healthy adolescents. In a longitudinal study of 8 healthy subjects aged 11 to 17.5 the greatest mean increase in white matter volume was found in frontal lobes (ranging from 8.4 -26.8%) across the two time points, indicating rapid maturation of these regions during late adolescence compared to other brain regions (Riddle et al, 2008). Subcortical tracts (extending into frontal regions) and corticospinal tract continue to undergo change up to age 25 (Lebel, Walker, Phillips & Beaulieu, 2008), and there is some indication that maturational change may continue to age 30 in superior temporal cortex (Sowell et al, 2003).…”
Section: Morphological Maturation Of Anterior Structuresmentioning
confidence: 89%
“…Gogtay et al, (2004) found that changes in gray matter volume follow a non-linear pattern across different brain regions, with loss of gray matter density (either through synaptic pruning or intracortical myelination - Paus, 2005) to dorsolateral prefrontal cortex and posterior superior temporal gyrus only evident after age 16-17 years in healthy adolescents. In a longitudinal study of 8 healthy subjects aged 11 to 17.5 the greatest mean increase in white matter volume was found in frontal lobes (ranging from 8.4 -26.8%) across the two time points, indicating rapid maturation of these regions during late adolescence compared to other brain regions (Riddle et al, 2008). Subcortical tracts (extending into frontal regions) and corticospinal tract continue to undergo change up to age 25 (Lebel, Walker, Phillips & Beaulieu, 2008), and there is some indication that maturational change may continue to age 30 in superior temporal cortex (Sowell et al, 2003).…”
Section: Morphological Maturation Of Anterior Structuresmentioning
confidence: 89%
“…For each subject, the T1-weighted MR image volume was used to define the binary ROI with the methods described by Riddle et al (25). Briefly, the T1-weighted MR image volume of each subject was aligned with a reference brain with a rigid transform (3 translation vectors and 3 rotation angles), then the deformation field between the reference brain and the globally aligned T1-weighted MR image volume was calculated with a nonrigid demons registration algorithm (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…For each subject we sampled axial PiB image slices from several different brain regions, including the occipital lobe and the bilateral temporal, parietal, and frontal lobes. The T1-weighted MRI volume was used to define these regions using the methods described by Riddle et al 21 Briefly, these anatomical regions were obtained by aligning the subject’s T1-weighted MRI volume (acquired at a time point close to the PiB PET baseline scan) with the T1-weighted MRI volume from a reference brain where the regions were segmented manually. The deformation field between the reference brain and the subject’s T1-weighted MRI volume was calculated with a nonrigid demons registration algorithm.…”
Section: Methodsmentioning
confidence: 99%